ДЕГРАМАТИКАЛІЗАЦІЯ В АНГЛІЙСЬКІЙ МОВІ ЯК СИСТЕМНЕ ЯВИЩЕ - Гирин, О.В. (Studia Philologica, 2014)
The article covers the main types of degrammatization in present-day English. It argues that presentday English observes degrammatization as a systemic phenomenon which covers both morphological and syntactic levels of the language. The reduction of the grammatical features in the language unit happens while one of the following processes: deaffixation, conversional and syntactic degrammatization, degrammatization of modal verbs and tense forms of the verb. These changes may be accompanied by adjoining processes: categorical, pragmatic and semanticreinterpretation, syntactic context narrowing, decreasein the usage frequency, phonologic position strengthening.